2015
DOI: 10.1111/liv.12774
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility and safety of the first interferon‐free therapy against hepatitis C in a real‐world setting

Abstract: With the better safety profile of interferon-free therapies, eligibility for HCV treatment will expand broadly, including patients with decompensated cirrhosis. Current limitations are renal failure and concomitant cardiac disease. Patients with advanced cirrhosis still have a high risk for hospitalization even with interferon-free therapies, but can continue HCV treatment in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Overall, the treatment was well tolerated, with few severe side effects. Similar results were reported in studies based on real world data such as TRIO and TARGET 2.0 trials [15][16][17][18]. A recent real world data-based study published from Canada on efficacy of SOF-based treatment reported overall SVR rates of 85% in all genotypes [19].…”
Section: Introductionsupporting
confidence: 71%
“…Overall, the treatment was well tolerated, with few severe side effects. Similar results were reported in studies based on real world data such as TRIO and TARGET 2.0 trials [15][16][17][18]. A recent real world data-based study published from Canada on efficacy of SOF-based treatment reported overall SVR rates of 85% in all genotypes [19].…”
Section: Introductionsupporting
confidence: 71%
“…As virological failures during therapy are rare, no stopping criteria have yet been established. Moreover, these regimens are far better tolerated than any of the former IFN-containing treatments [14,33,70,71]. Thus, there seems to be no major interest in shortened treatment durations with respect to drug safety.…”
Section: Cut-off Definitionmentioning
confidence: 90%
“…Early mortality due to aggravation of liver function during therapy might occur as was observed during treatment with lamivudine for decompensated HBV-LC [40] . Patients with advanced cirrhosis still have a high risk for hospitalization after the initiation of DAA treatment [36] . In addition, decompensated cirrhosis patients are more prone to develop drug-induced sideeffects when compared to patients with compensated cirrhosis.…”
Section: Expectations and Concerns Of Daa Treatment For Decompensatedmentioning
confidence: 99%
“…Actually, preliminary report showed that DAAs for decompensated LC improved MELD scores in 60% to 79% patients only 4 wk after treatment finalization [31] . For these reasons, DAA treatments would be indicated positively for those with decompensated LC-HCV in real world-settings [36] . Despite of these encouraging situations and that a standardized mortality rate analysis reported a lower liver-related mortality among HCV-cirrhotics with SVR by IFN treatment [37] , to our knowledge there are currently no data on disease progression, delisting from LT, and improvement of life expectancy after the achievement of SVR for decompensated LC-HCV.…”
Section: Expectations and Concerns Of Daa Treatment For Decompensatedmentioning
confidence: 99%